Textural and rheological properties of stevia ice cream - Pon, S. Y.; Lee, W. J.; Chong, Gun Hean (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Ice cream contains high sugar content and therefore it is in contradiction with the concept of healthy diet. The objective of this study is to determine the suitability of using stevia as an alternative natural sweetener in making ice cream. In- house ice cream formulation (as the control) and three different concentrations of stevia ice cream formulations of (A, B and C) were used. Physical properties of the ice cream such as the overrun, total soluble solid, meltdown rate, rheology, and textural properties were evaluated. All ice cream samples exhibited a non-Newtonian flow with pseudoplastic behavior. Stevia ice cream has a lower melting rate and has a higher sustainability. The power law also showed that apparent viscosities of stevia ice cream were higher. Therefore, stevia can be used as a natural sugar substitute in ice cream production.